Bio‐waste derived carbon nano‐onions as an efficient electrode material for symmetric and lead‐carbon hybrid ultracapacitors. (23rd May 2022) - Muduli, Sadananda; Pati, Subir K.; Martha, Surendra K.
Summary: Carbon and metal oxide nanocomposites have been extensively studied as electrode materials to develop energy and power‐dense supercapacitors in recent years. Nevertheless, nano carbons with improved porosity and functional moieties are the most eco‐friendly and cost‐effective supercapacitor materials. In this work, carbon nano‐onions (CNOs) synthesized by a single‐step flame soot collection method, subsequently calcined at 600°C in an inert environment (CNO‐600), are used as electrode material for the supercapacitors. CNO‐600 s have a layer‐by‐layer nano onion structure with a ~25 nm particle size and a Brunauer–Emmett–Teller surface area of 147 m 2  g −1 . CNO‐600 delivers 266 and 186 F g −1 of capacitance at 0.5 A g −1 for half cells and symmetric ultracapacitors, respectively. Ultracapacitors show capacitance retention of 91% with 20 000 GCD cycles in 1 M H2 SO4 electrolyte. The stable capacitance of CNO‐600 is due to easy intercalation/de‐intercalation of electrolyte ions and electrons in the layer‐by‐layer structure of CNOs, contributing to pseudocapacitive charge storage with electric double layer capacitor behavior. The lead‐carbon hybrid ultracapacitor fabricated using CNO‐600 as anode material and PbO2 as cathode delivers a specific capacitance of 515 F g −1 at 1 A g −1 in 4.5 M H2 SO4 electrolyte in the voltage range of 2.3 and 0.6 V. The substantial improvement of charge storage in CNO‐based symmetric and lead‐carbon hybrid system, demonstrate an excellent opportunity for the development of high‐performance supercapacitors. Abstract : Carbon nano‐onions (CNOs) synthesized by a single‐step flame soot collection method, subsequently calcined at 600°C in an inert environment (CNO‐600), are used as electrode material for the hybrid ultracapacitors. The lead‐carbon hybrid ultracapacitor fabricated using CNO‐600 as anode material and PbO2 as cathode delivers a specific capacitance of 515 F g −1 at 1 A g −1 in 4.5 M H2 SO4 electrolyte in the voltage range of 2.3 and 0.6 V, demonstrate an excellent opportunity for the development of high‐performance supercapacitors.